Przygotowanie do małżeństwa w świetle Directorio de la pastoral familiar de la Iglesia en España - Adamczyk, Jerzy (Ius Matrimoniale, 2016)
This article tells about preparation to marriage acording to Directorio de la pastoral familiar de la Iglesia en Espana. The article provides further, proximal and direct preparation to marriage. In the first part it is said about further preparation to marriage. In the second part it is pointed proximal preparation to marriage. The third part treats of direct preparation to the celebration of sacrament of marriage.